(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Herbal medicines offer vast scope for the successful treatment of urolithiasis. Although most remedies were herbal and proved useful, a systematic scientific evaluation has been reported for only few remedies. Tecoma stans a herbal formulation was claimed to be useful in the treatment of urinary stones. Toxicity study confirms that the therapeutic dose of Tecoma stans was 430 mg/kg. The antilithiatic effect of Tecoma stans was determined on lactose diet + ethylene glycol induced and ammonium chloride + ethylene glycol induced lithiasis in male albino wistar rats. The results obtained after 4 weeks of treatment for the urine estimation of calcium, oxalate, magnesium and protein were significant (p<0.01) in reducing the calculus when compared with the standard drug cystone (750 mg/kg) treated animals. Urine calcium oxalate crystals were also reduced in test drug treated and standard treated groups. These observations and results conclude that Tecoma stans herbal formulation possesses significant antiurolithiatic activity.